Futurist arte / vita: Benedetta Fictionalized - Larkin, Erin (Volume 8 2018, 2018)
Keywords: dept.wll

The Minor Tone of Desire - Barros, Pía; Cardone, Resha (Ediciones Sherezade, 2018)
Keywords: 21st century; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; dept.wll; faculty_collection

Promoting social justice with CALL - Gleason, Jesse; Suvorov, Ruslan (CALICO Journal, 2018)
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-216-002-732-944, pop00223 tex.type: [object Object]
Keywords: dept.wll; peer-reviewed

Farewell to Naples: Ferrante’s 'Story of a New Name' - Palma, Pina (Forum Italicum: A Journal of Italian Studies, 2018)
In Ferrante’s Story of a New Name, the protagonist’s journey to self-knowledge and self-realization is mapped through a farewell trip to Naples before she begins her studies in Pisa. As the centerpiece and background around and against which Elena’s accomplishments, failures, and societal pressures revolve, Naples emerges as a mosaic of energy and lethargy, unbreakable traditions and negligible innovations. While these elements mirror the protagonist’s powerlessness in changing the “norms” to which she is expected to adhere, they also function as her spur to a steady shift toward self-understanding. In this article, I analyze the ways in which Ferrante’s use of the beauty and lure, corrosiveness and lethality of Naples parallel her discourse on the protagonist’s search for self-understanding, a process that will ultimately enable Elena, the protagonist, to find self-realization. © 2018, The Author(s) 2018.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-690-228-679-585, pop00335 tex.type: [object Object]
Keywords: authorship; dept.wll; labyrinth; memory; peer-reviewed; reading; self-fulfillment; self-knowledge; urban space

The devil and the mirror: Pulci’s theology - Palma, Pina (Luigi Pulci in Renaissance Florence and Beyond, 2018)
Keywords: dept.wll

Connected classrooms: Videoconferencing in TESOL teacher preparation - Schmitt, Elena; Eilderts, Luke (International Journal of Teaching and Learning in Higher Education, 2018)
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found

Class, generation, and gender in Esther Tusquets's Habíamos Ganado La Guerra: Reflections on the winning of the Spanish Civil War - Weng, Miaowei (Hispanófila, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll; peer-reviewed

Patterns of oral choice and evaluation across secondary content areas. - Gleason, Jesse; Berg, Margaret A; Huang, Jingzi (Language and Education, 2018)
Our study focuses on Choice and Evaluation, two of Mohan's knowledge structures to uncover how teachers and students across content areas developed disciplinary knowledge through classroom talk. Participants included in-service teachers and their students in rural and urban secondary schools in the Eastern and Western US. Through Choice and Evaluation, we examined opportunities for students across four disciplines to build up their knowledge of content matter or field. Findings revealed that teachers of math and science built students' field knowledge through classroom exploration, eliciting Evaluation in dialogic patterns involving Choice, while social studies and language arts teachers helped students implicitly use Choice/Evaluation through projects based on their previous experiences. The essential role of student background knowledge in enabling participation across different types of oral exchanges is shown. This study uncovers tendencies across classrooms and makes linguistically informed suggestions for teachers in the disciplines.
0 citations (Crossref) [2023-10-31] Citation Key Alias: gleasonPatternsOralChoice2018, lens.org/109-314-805-638-437 tex.type: [object Object]
Keywords: Teacher education; classroom discourse; dept.wll; language across content; peer-reviewed